2011
DOI: 10.2147/opth.s23091
|View full text |Cite
|
Sign up to set email alerts
|

Hearing disability in patients with Fuchs’ endothelial corneal dystrophy: unrecognized co-pathology?

Abstract: PurposeTo investigate a possible association between Fuchs’ endothelial corneal dystrophy (FECD) and hearing disability.MethodsA cross-sectional observational study was performed at the University Medical Center Utrecht. Cases and controls were patients who were treated by a cornea specialist between 2004 and 2008. FECD patients had either already undergone or were planned for a keratoplasty procedure. All controls were patients treated for cataract without any corneal pathology. Cases and controls were matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Hearing defects found in individuals with FECD (13) and Harboyan syndrome (6) are mirrored in slc4a11 −/− mice (12,14). These mice manifest normal levels of K + in the inner ear's endolymph and evidence of extracellular oedema in the fibrocytes underlying the stria vascularis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Hearing defects found in individuals with FECD (13) and Harboyan syndrome (6) are mirrored in slc4a11 −/− mice (12,14). These mice manifest normal levels of K + in the inner ear's endolymph and evidence of extracellular oedema in the fibrocytes underlying the stria vascularis (12).…”
Section: Discussionmentioning
confidence: 99%
“…FCD was a genetic disorder of the corneal endothelium and was the most common cause of corneal transplantation. Recently, Stehouwer et al reported that rate of hearing disability in FCD group was higher than control group [16]. It suggested an association between FCD and hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…27 Genetic heterogeneity may exist for CHED2 as some families have no SLC4A11 mutation detected, 12,13,22,25,28 however, only one CHED2 locus has been mapped. 3,4,29 Recently in a study of a non-consanguineous CHED2 Thai family all affected individuals were found to be compound heterozygotes for a novel missense mutation (K260E) and a 68kb deletion which encompasses the SLC4A11 gene; 30 this type of mutation may be the cause of disease in families in which an SLC4A11 gene mutation has not been identified to date.…”
Section: Discussionmentioning
confidence: 99%